(3Gdbhd GdeCfhS HaJM eZdb GdbGehSs - (3HOQ GdOjf GdbQGai (B1008s; (3eMeO Hf jYbhH Hf eMeO, eLO GdOjf GdajQhRGHGOj,J (B817 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi Rjf ef GQGO HGdJLdi HCTQa GddZGJ hHYO adG jNai Cf Yde GddZI ef CTQa GdYdhe hGdhbha Ydi ZhGeVI ef CLd GdeYdhe s
(3BNQgG (B:s
(3aWQH GdMGVQhf EdG GdeHQO aYLH efg hWQH GdeHQO ef gPG GdLhGH MJi Tb KhHI GfJgi s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B147s
(3JHUQGJ GdCUd (B:s
Keywords: (3eJaQbGJs